Existence of Solutions of a Riccati Differential System from a General Cumulant Control Problem - Stanley R. Liberty; Libin Mou (International Journal of Differential Equations)
We study a system of infinitely many Riccati equations that arise from a cumulant control problem, which is a generalization of regulator problems, risk-sensitive controls, minimal cost variance controls, and k-cumulant controls. We obtain estimates for the existence intervals of solutions of the system. In particular, new existence conditions are derived for solutions on the horizon of the cumulant control problem.